Evaluating Flash Flood Hazards in West Sumatra: Insights from Topographic and Meteorological Data - Riki Chandra Wijaya; Umboro Lasminto (Rekayasa, 2026)
Flash floods, defined by the rapid flow of water mixed with landslide debris, represent a significant threat to areas with sloped or mountainous terrains. In Tanah Datar Regency, West Sumatra, a region dominated by hills and mountains, these natural disasters are particularly concerning due to the region’s topographical and meteorological characteristics. The steep slopes and high rainfall intensity create conditions favorable for large-scale debris flows, making this area highly vulnerable to flash floods. To understand the extent of this hazard, a numerical analysis was conducted using topographic and meteorological data, incorporating rainfall records from 2020 to 2023. The analysis revealed a peak flow discharge of approximately 1017.3 cubic meters per second (m³/s), which has the potential to cause riverbank flooding extending 15 to 30 meters beyond the river boundaries. This level of discharge poses significant risks to communities living near rivers, as the flooding could result in substantial damage to property, infrastructure, and livelihoods. Moreover, the numerical models suggest that future discharges may surpass the recorded peak levels, further increasing the potential for catastrophic impacts. These findings highlight the urgent need for increased awareness and preparedness among the population, particularly those residing along riverbanks. Proactive measures, such as the implementation of early warning systems, improved disaster education, and reinforcement of riverbanks, are critical to mitigating these risks. Additionally, sustainable land-use practices and stricter regulations on hillside developments can help reduce the likelihood of landslides contributing to debris flows. With coordinated efforts from local authorities, policymakers, and the community, the resilience of Tanah Datar Regency can be enhanced, minimizing the devastating consequences of flash floods in the future.